سلوكيات المواطنة التنظيمية وعلاقتها بتنمية رأس المال الفكري : دراسة ميدانية على العاملين الإداريين بشؤون التربية والتعليم بمدينة درنة في ليبيا - جبريل، وائل محمد Jebril, Wael Mohammed (جامعة جرش, 2015)
هدفت الدراسة إلى التعرف على مستوى سلوكيات المواطنة التنظيمية لدى العاملين الإداريين بشؤون التربية والتعليم بمدينة درنة في ليبيا من خلال الأبعاد الآتية: (الإيثار، الكياسة، السلوك الحضاري، الروح الرياضية، الالتزام العام)؛ كما هدفت الدراسة إلى التعرف على مستوى تنمية رأس المال الفكري للعاملين الإداريين محل الدراسة من خلال المحاور التالية: (تنمية رأس المال البشري، تنمية رأس المال الهيكلي، تنمية رأس مال العلاقات)، بالإضافة إلى التعرف على طبيعة العلاقات بين سلوكيات المواطنة التنظيمية وتنمية رأس المال الفكري، ولتحقيق أهداف الدراسة، اتبعت الدراسة منهج دراسة الحالة، فقد قام الباحث بتطوير استبانة معتمداً على بعض الدراسات السابقة، حيث تم التأكد من مصداقيتها ومعامل الثبات لها، وقد تمثل مجتمع الدراسة في جميع العاملين الإداريين بشؤون التربية والتعليم بمدينة درنة الليبية، والذي بلغ قوامه بـ (264) عامل إداري، وقد اتبعت الدراسة أسلوب المسح الشامل، وبعد توزيع الاستبانة تم استرجاع (188) استمارة صالحة للتحليل الإحصائي، ولتحليل بيانات الدراسة تم الاستعانة بالحاسب الآلي واستخدام برنامج إحصائي من خدمة البرمجيات الواردة في (SPSS) وفقاً للنسب المئوية والمتوسطات الحسابية والانحرافات المعيارية، واختبار T، معامل ارتباط بيرسون، حيث تم التوصل إلى العديد من النتائج يمكن إيجازها فيما يلي: كشفت الدراسة أن المستوى العام لسلوكيات المواطنة التنظيمية لدى العاملين الإداريين بشؤون التربية والتعليم محل الدراسة جاء مرتفعاً، كما بينت الدراسة أن المستوى العالم لتنمية رأس المال الفكري جاء متوسطاً، أظهرت الدراسة أيضاً وجود علاقة ذات دلالة إحصائية بين سلوكيات المواطنة التنظيمية وتنمية رأس المال الفكري عند مستوى دلالة معنوية (1%)، وأخيراً قدمت الدراسة مجموعة من التوصيات التي يؤمل ابتاعها للرفع من مستوى تنمية رأس المال الفكري وتدعيم توافر سلوكيات المواطنة التنظيمية لدى العاملين بشؤون التربية والتعليم في ليبيا.
The study aimed to identify the level of organizational citizenship behaviors for administrative personnel affairs of Education in Derna, Libya through the following dimensions: (Altruism, courteous, civilized behavior, sportsmanship, public commitment). The study also aimed to identify the level of intellectual capital development in relation to the affairs of Education under study through the following themes: (Human capital development, the structural capital development, capital development of relations). Besides identifying the nature of the relationship of the influential orgaoi2lltional citizenship behaviors on intellectual capital development. To achieve its objectives, the study applied the case study method; the researcher developed a question Dllire based on some previous studies, which he was sure of their validity and reliability. The study population is represent in the administrative personnel, almost (264) administrative, at the affairs of Education, city of Derna, Libya. The study followed the method of comprehensive survey and after the distribution of the questionnaire, (188) form have been retrieved and were suitable for statistical analysis. The analysis of the study data was done by the computer, by the use of statistical software from the software set service (SPSS) in accordance with the percentages, Arithmetic Mean and standard deviations, T. test, Person's Correlation Coefficient, which Jed to the following results that are summarized below: The study revealed that the overall level of OCB among the administrative personnel at the affairs of Education under study was high. The study also showed that the overall level of ICD from the perspective of administrative personnel under study came average. Moreover, it showed the presence of a relationship with statistically significant differences between OCB and ICD at the level of significance (1%). Finally, the study provided a set of recommendations that will hopefully be followed in order to raise the level of ICD and strengthening availability of organizational citizenship behaviors among administrative at the affairs of Education in Libya.
Keywords: المواطنة التنظيمية -- رأس المال الفكرى -- شؤون التربية والتعليم -- مدينة درنة -- ليبيا